Membuka Ruang Baru Demokrasi Partisipatif Bagi Community Policing: Peran Forum Warga - Thamrin, Djuni (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2017)
This paper argues to push and open participative democratization space for citizens, particularly the destitute and marginalized, to actively participate in public decision-making that implicates their future quality of life, including involvement in community policing or Polmas. Examples from all over the world identified from various studies show that the more expansive and intensive the participation involvement of citizens in a country's governance, development continuity will be cheaper and easier to push towards.